1983
DOI: 10.2214/ajr.141.5.959
|View full text |Cite
|
Sign up to set email alerts
|

The pelvis after surgery for rectal carcinoma: serial CT observations with emphasis on nonneoplastic features

Abstract: Ten asymptomatic patients who had undergone resection of rectal carcinoma were evaluated prospectively by at least three serial computed tomographic (CT) examina tions of the pelvis within 24 months of surgery. Of the seven patients who had undergone abdominoperineal resection, five were found to have a presacral mass due to normal postoperative changes within the first 4 months. The mass showed a variable diminution between 4 and 9 months after operation and developed a more distinct outline, partial separati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
7

Year Published

1985
1985
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(17 citation statements)
references
References 12 publications
(13 reference statements)
1
9
0
7
Order By: Relevance
“…Radiological detection of locally recurrent disease can be challenging. A soft tissue mass may persist in the pelvis for 24 months or more following surgery in the absence of recurrence, and this appearance is enhanced by previous radiotherapy or pelvic sepsis due to postoperative anastomotic leakage. Recurrence may be suspected by changes detected over serial scans, and CT‐guided biopsy of accessible suspicious areas may be possible.…”
Section: Imaging and Stagingmentioning
confidence: 99%
“…Radiological detection of locally recurrent disease can be challenging. A soft tissue mass may persist in the pelvis for 24 months or more following surgery in the absence of recurrence, and this appearance is enhanced by previous radiotherapy or pelvic sepsis due to postoperative anastomotic leakage. Recurrence may be suspected by changes detected over serial scans, and CT‐guided biopsy of accessible suspicious areas may be possible.…”
Section: Imaging and Stagingmentioning
confidence: 99%
“…Computer tomography imaging often is sup- plemented with information from MRI and/or endoluminal ultrasound scans in addition to clinical examination and endoscopy. Initially it was reported that MRI had a greater ability to differentiate between scar and tumor recurrence than CT [42][43][44][45][46] ; however, more recent results have raised doubts about these findings. 47,48 CT and MRI are both accurate at detecting pelvic masses after colorectal surgery, but they often are unreliable in distinguishing between scar and tumor recurrence.…”
Section: Differentiation Between Scar and Locallymentioning
confidence: 99%
“…The mass is usually located in the midline and homogeneous in density on CT, and does not increase in size with time. The CT criteria that suggest recurrent cancer include invasion of adjacent structures, increased size, heterogeneity of the contents of the mass, asymmetry, associated lymphadenopathy and peritoneal carcinomatosis [9]. In this regard, imaging techniques can provide useful information, and particularly CT imaging, which allows a complete assessment of the pelvis, including clinically inaccessible areas.…”
Section: Differentiation Between Radiation-induced Damage and Recurrementioning
confidence: 99%